Constitutional Amendment in the e-Democracy Era: Experience Constitutional “Crowdsourcing” from Iceland and Challenges for Indonesia - Nggilu, Novendri; Zulkifli; Yassine, Chami; Apripari; Kaluku, Julisa Aprilia; Mohammad AbdAllah Alshawabkeh (Jurnal Suara Hukum, 2025)
The growing interest in constitutional reform has drawn attention to crowdsourcing as an innovative method for increasing public involvement. This approach, successfully implemented in Iceland, contrasts sharply with the traditionally elitist processes seen in many other countries, including Indonesia. This article investigates the potential of applying a crowdsourced model to Indonesia’s future constitutional amendment processes. Using a statutory and comparative legal method, the study analyzes the Icelandic experience to draw insights for the Indonesian context. The research finds that Indonesia's constitutional amendment process has historically marginalized public participation, lacking transparency and inclusivity. In contrast, Iceland's model demonstrates that structured digital engagement can produce a more democratic and representative outcome. This study offers two key contributions: first, it highlights the normative shift introduced by digital constitutionalism; second, it underscores the importance of designing hybrid models that blend conventional and digital mechanisms. While promising, the implementation of such a model in Indonesia faces significant obstacles, including digital inequality, manipulation risks from political buzzers, and the ethical challenges of AI-mediated discourse. These findings suggest that any future reform must be carefully tailored to local conditions, ensuring both accessibility and legitimacy